2005
DOI: 10.1002/jssc.200500108
|View full text |Cite
|
Sign up to set email alerts
|

LC‐MS/MS in the elucidation of an isomer of the recreational drug methylenedioxy ethylamphetamine: Methylenedioxy dimethylamphetamine

Abstract: This paper describes the surplus value of a quadrupole-orthogonal acceleration TOF mass spectrometer, coupled to a liquid chromatographic separation system, for the unequivocal identification and structural elucidation of an unknown compound in the field of designer drugs. In a patient sample set (blood, tissues, vitreous humor, etc.), analyzed with a dedicated liquid chromatographic-fluorescence detection method for the determination of methylenedioxy amphetamine, methylenedioxy methamphetamine, and methylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…[33] Tramadol and O-desmethyl venlafaxin sharing a molecular formula of C 16 H 25 NO 2 and [M+H] + 264.1958, have been reported to undergo similar fragmentation, [34] yielding only a single fragment of m/z 58. Similar results have been reported about isomers that could not be distinguished based on their fragments, including the compounds studied in the present work (MDEA and MDDMA, [35] and ephedrine and pseudoephedrine [36] ). Similar results have been reported about isomers that could not be distinguished based on their fragments, including the compounds studied in the present work (MDEA and MDDMA, [35] and ephedrine and pseudoephedrine [36] ).…”
Section: Resultssupporting
confidence: 90%
“…[33] Tramadol and O-desmethyl venlafaxin sharing a molecular formula of C 16 H 25 NO 2 and [M+H] + 264.1958, have been reported to undergo similar fragmentation, [34] yielding only a single fragment of m/z 58. Similar results have been reported about isomers that could not be distinguished based on their fragments, including the compounds studied in the present work (MDEA and MDDMA, [35] and ephedrine and pseudoephedrine [36] ). Similar results have been reported about isomers that could not be distinguished based on their fragments, including the compounds studied in the present work (MDEA and MDDMA, [35] and ephedrine and pseudoephedrine [36] ).…”
Section: Resultssupporting
confidence: 90%
“…Coinjection of the pure (in-house synthesized) MDDM together with a blood extract unequivocally identified the unknown compound as MDDM [8]. Calibrators containing increasing amounts of MDDM in various matrices were made.…”
Section: Resultsmentioning
confidence: 99%
“…The unknown substance was detected when screening some extracts (blood, urine, or tissue) for the presence of amphetamine and methylenedioxyamphetamine designer drugs, applying a previously described LC-MS/MS method [7]. Thorough investigation of the literature and of the obtained MS/MS spectrum (precursor and product ions) revealed that the initially unidentified molecule was MDDM [8]. Due to the presence of a 1,000-fold higher amount of MDMA and to the lack of selectivity, other techniques, such as HPLC-diode array detection (HPLC-DAD) and GC-MS, had failed to demonstrate the presence of the unknown designer drug.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations